2017
DOI: 10.1186/s13041-017-0291-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of A-to-I editing in human and non-human primate brains reveals conserved patterns and context-dependent regulation of RNA editing

Abstract: A-to-I RNA editing is an important process for generating molecular diversity in the brain through modification of transcripts encoding several proteins important for neuronal signaling. We investigated the relationships between the extent of editing at multiple substrate transcripts (5HT2C, MGLUR4, CADPS, GLUR2, GLUR4, and GABRA3) in brain tissue obtained from adult humans and rhesus macaques. Several patterns emerged from these studies revealing conservation of editing across primate species. Additionally, v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 24 publications
(27 reference statements)
1
19
0
Order By: Relevance
“…Also, it has been shown that GABRA3 is targeted by both ADARs enzymes (Ohlson et al, 2007). Interestingly, the editing site on GABRA3 was already reported in different animals such as human (Nicholas et al, 2010, O'Neil et al, 2017, mouse (Daniel et al, 2011), pig (Venø et al, 2012), bovine (Bakhtiarizadeh et al, 2018), rat, rabbit, dog, frog (Daniel et al, 2011) and chicken embryos (Daniel et al, 2011, Frésard et al, 2015. This result suggests that editing events may contribute to amino acid functional conservation throughout the evolution of vertebrates, as has been reported in previous study in chicken (Roux et al, 2016).…”
Section: )supporting
confidence: 76%
“…Also, it has been shown that GABRA3 is targeted by both ADARs enzymes (Ohlson et al, 2007). Interestingly, the editing site on GABRA3 was already reported in different animals such as human (Nicholas et al, 2010, O'Neil et al, 2017, mouse (Daniel et al, 2011), pig (Venø et al, 2012), bovine (Bakhtiarizadeh et al, 2018), rat, rabbit, dog, frog (Daniel et al, 2011) and chicken embryos (Daniel et al, 2011, Frésard et al, 2015. This result suggests that editing events may contribute to amino acid functional conservation throughout the evolution of vertebrates, as has been reported in previous study in chicken (Roux et al, 2016).…”
Section: )supporting
confidence: 76%
“…We used the mmPCR-seq method to detect A-to-I editing at 146 pre-selected sites in two regions in the rat brain. While changes in A-to-I RNA editing in the rat were previously demonstrated in cortical cultures and brain samples [ 50 , 51 , 53 , 54 ], this is the first use of mmPCR-seq to quantify editing changes in rat brain tissue at multiple sites. For some sites (e.g., Celf4 , Ankrd28 ), editing is demonstrated for the first time in the rat; editing levels at these sites is largely conserved with the corresponding human and mouse orthologs.…”
Section: Discussionmentioning
confidence: 86%
“…2 and Fig. 4 , raising the concern that PFC samples were contaminated during extraction with choroid plexus (CP) tissue (where Htr2c expression is high but A and B site editing levels are low) [ 51 ]. We thus assessed the expression of the CP marker Coagulation factor V F5 [ 52 ] in O1-C ( n = 5) and O1-PRS ( n = 6) samples with both low and high A and B site editing.…”
Section: Resultsmentioning
confidence: 99%
“…The calcium‐dependent secretion activator 1 (CADPS) is shown to participate in calcium‐dependent release of synaptic vesicles . This was the only protein from our list whose ortholog was also edited in the fruit fly proteome .…”
Section: Resultsmentioning
confidence: 99%